KONTRIBUSI JOB DEMANDS DAN JOB RESOURCES TERHADAP WORK ENGAGEMENT - Amelia Amelia; Herman Sjahruddin; Alimuddin Syar (Jurnal Bina Bangsa Ekonomika, 2024)
Employees are the focus of achieving agency success so that employees are required to maximize their performance in supporting the achievement of agency goals. In practice, agencies really need employees who can always be actively involved in the tasks and/or work given to them. Work engagement is a positive behavior that can encourage employee effectiveness which in turn increases agency effectiveness. The study is oriented towards explaining the contribution of job demands and job resources to the work engagement of 45 employees of the PUPR (Public Works and Public Housing) Region VIII Makassar Competency Development Center. Data analysis was carried out using multiple linear regression using SPSS 27.0. Hypothesis testing showed evidence that job demands made a positive and significant contribution to work engagement while job resources contributed negatively and insignificantly to work engagement